2021
DOI: 10.1186/s12951-021-00894-5
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from pioglitazone-pretreated MSCs accelerate diabetic wound healing through enhancing angiogenesis

Abstract: Background Enhanced angiogenesis can promote diabetic wound healing. Mesenchymal stem cells (MSCs)-derived exosomes, which are cell-free therapeutics, are promising candidates for the treatment of diabetic wound healing. The present study aimed to investigate the effect of exosomes derived from MSCs pretreated with pioglitazone (PGZ-Exos) on diabetic wound healing. Results We isolated PGZ-Exos from the supernatants of pioglitazone-treated BMSCs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(104 citation statements)
references
References 68 publications
3
101
0
Order By: Relevance
“…MSC-EXO exert beneficial effects via bioactive substances that include proteins, mRNAs, LncRNA and miRNAs. Notably, the substances in MSC-EXO are largely influenced by environmental stimuli that alters their biological effect [ 20 , 21 ]. Thus, optimizing MSC-EXO in vitro to enhance their therapeutic effects is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…MSC-EXO exert beneficial effects via bioactive substances that include proteins, mRNAs, LncRNA and miRNAs. Notably, the substances in MSC-EXO are largely influenced by environmental stimuli that alters their biological effect [ 20 , 21 ]. Thus, optimizing MSC-EXO in vitro to enhance their therapeutic effects is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Exos are small membrane vesicles originating from intracellular corpuscles, exhibiting a diameter of about 30–200 nm, which are packed with various proteins, lipids, and RNA. These vesicles can be released into extracellular fluid, blood, and cerebrospinal fluid by cells of all living systems [ 5 , 6 ]. Under physiological and pathophysiological conditions, they are capable of transferring their cargo between source cells and target cells via extracellular fluid, blood, and cerebrospinal fluid, and they critically impact intercellular communication [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies displayed that exosomes are a treatment modality that may offer a promising therapeutic strategy for tissue regeneration [ 32 , 33 ]. Exosomes have received extensive attention because they were reported to possess functional proteins and miRNAs that have many positive impacts in mediating cellular function and treating a variety of diseases [ 16 , 34 , 35 ]. Recent studies indicated that MSCs-Exos protect endplate chondrocytes against death and offer a potential strategy for IVD degeneration [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was approved by the Clinical Research Ethics Committee of Tongji Medical College, Huazhong University of Science and Technology. According to our previous research, SD rats were isolated BMSCs [ 16 , 23 ]. Briefly, the bone marrow of the femur and tibia was washed with a syringe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation